Association between painful temporomandibular disorders, sleep bruxism and tinnitus - Fernandes, Giovana; Siqueira, José Tadeu Tesseroli De; Gonçalves, Daniela Aparecida De Godoi; Camparis, Cinara Maria (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2014)
The present cross-sectional study was designed to investigate the association between sleep bruxism (SB), tinnitus and temporomandibular disorders (TMD). The sample consisted of 261 women (mean age of 37.0 years). The Research Diagnostic Criteria for Temporomandibular Disorders were used to classify TMD and self-reported tinnitus. SB was diagnosed by clinical criteria proposed by the American Academy of Sleep Medicine. The results showed an association between painful TMD and tinnitus (OR = 7.3; 95%CI = 3.50-15.39; p < 0.001). With regard to SB, the association was of lower magnitude (OR = 1.9; 95%CI = 1.16-3.26; p < 0.0163). When the sample was stratified by the presence of SB and painful TMD, only SB showed no association with tinnitus. The presence of painful TMD without SB was significantly associated with tinnitus (OR = 6.7; 95%CI = 2.64-17.22; p < 0.0001). The concomitant presence of painful TMD and SB was associated with a higher degree of tinnitus severity (OR = 7.0; 95%CI = 3.00-15.89; p < 0.0001). It may be concluded that there is an association between SB, painful TMD and self-reported tinnitus; however, no relationship of a causal nature could be established.
Keywords: Facial Pain; Sleep Bruxism; Tinnitus